Outreach and recruitment of African Americans for Alzheimer's disease studies during the COVID‐19 pandemic. (31st December 2021) - Starks, Takiyah D; Caban‐Holt, Allison M; Williams, Kelvin; Adams, Larry D; Haines, Johnathan L; Beecham, Gary W; Reitz, Christiane; Cuccaro, Michael L; Vance, Jeffery M; Pericak‐Vance, Margaret A; Byrd, Goldie S
Abstract: Background: Recruiting African Americans in AD studies remains a challenge, particularly during a pandemic, where major health disparities in this population are illuminated. The recruitment literature suggests myriad factors that contribute to the underrepresentation of AAs, including, but not limited to "mistrust" in researchers and their institutions. Maintaining a continuous presence in the AA community builds trust even when traditional outreach methods are not allowed. We continued to provide outreach and recruitment opportunities through COVID education and food for families as we educated them about AD, and opportunities for study participation. Method: While our traditional outreach methods for recruiting AAs were interrupted, we continued to conduct AD outreach using virtual platforms, mobile phone calls, family conference calls and food distributions. We hosted nine webinars on COVID‐19 to maintain a presence in local and national AA communities and to remain connected to existing AD participants. We reached over 160, 000 persons through webinars and social media. We established new relationship new faith leaders in the AA community who co‐hosted COVID‐19 webinars and also expressed interest in forming partnerships on AD education. In addition, we hosted food drives in AA communities that not only addressed food insecurity and COVID prevention, but also AD education and AD research opportunities. At the food drives we distributed bags with masks, hand sanitizers, AD brochures, booklets and study participation information. Result: Between October and December of 2020, 64 AAs who attended food drives expressed interest in AD studies that required blood draws and cognitive testing. Fifteen enrolled in our genetic study, 15 requested additional follow‐up and 13 expressed interest in participating in more than one study. Conclusion: Prior research suggests that recruiting AAs into AD studies requires continuous engagement. We used multiple strategies to maintain contact with the AA community and existing research participants, and successfully increased enrollment in the last quarter of the year. Maintaining consistent and continuous engagement facilitates trustworthiness with AAs and yields positive recruitment outcomes, even in a pandemic where traditional recruitment methods are limited.